2015
DOI: 10.1007/s00382-015-2637-7
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison and validation of the mixed layer depth fields of global ocean syntheses

Abstract: 5-7 (14-16) m with the vertical resolution of 25 (50) m when the criterion of potential density exceeding the 10-m value by 0.03 kg m −3 is used for the MLD estimation. Using the larger criterion (0.125 kg m −3 ) generally reduces the underestimations. In addition, positive biases greater than 100 m are found in wintertime subpolar regions when MLD criteria based on temperature are used. Biases of the reanalyses are due to both model errors and errors related to differences between the assimilation methods. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 53 publications
3
38
1
2
Order By: Relevance
“…1d, e), and produce h distributions that are similar to the reanalyses in the eastern Pacific and Atlantic, but significantly shallower in the central ocean basins. Toyoda et al (2015) show that monthly mean ocean mixed layer depths from de Boyer Montegut et al (2004) are more shallow than individual observed profiles due to rapid restratification in spring and vertical resolution issues. The Naval Research Lab (Kara et al 2003) annual mean mixed layer depth climatology is shown in Fig.…”
Section: Methodsmentioning
confidence: 98%
“…1d, e), and produce h distributions that are similar to the reanalyses in the eastern Pacific and Atlantic, but significantly shallower in the central ocean basins. Toyoda et al (2015) show that monthly mean ocean mixed layer depths from de Boyer Montegut et al (2004) are more shallow than individual observed profiles due to rapid restratification in spring and vertical resolution issues. The Naval Research Lab (Kara et al 2003) annual mean mixed layer depth climatology is shown in Fig.…”
Section: Methodsmentioning
confidence: 98%
“…Toyoda et al (2015) revealed that this definition results in an MLD field with less errors relative to definitions using other criteria for potential density (0.03 kg m −3 ) or potential temperature (0.2 and 0.5 °C) in terms of both the seasonal cycle and interannual variability since errors due to monthly averaging of profiles and to weak thermal stratification at high latitudes are relatively small with this definition. Moreover, we use only wintertime maximum MLDs, since we consider that such MLDs are thought to be a most important factor for the thermocline layer dynamics via water mass formation and subduction.…”
Section: Datamentioning
confidence: 99%
“…These syntheses/reanalyses are all different in ocean general circulation model, resolution, surface forcing, ML parameterization, assimilated data and assimilation method (see details in Toyoda et al 2015). MLDs are obtained from the monthly mean TS fields on the original grids for the individual datasets and then interpolated onto the common longitude-latitude grids at one-degree intervals.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The mixed layer depth (MLD) is estimated according to the difference in potential density (σ) between 10 m and the base of the mixed layer using a threshold of 0.125 kg m -3 (a reference for studies regarding subtropical gyres; e.g. Levitus, 1982;Ohno et al, 2004;Nicholson et al, 2015;Toyoda et al, 2015). 20…”
Section: Biogeochemical-argo Measurementsmentioning
confidence: 99%